THE INFLUENCE DATE AND LEVEL OF CUTTING ON GROWTH OF - A . M . Sultan (Mesopotamia Journal of Agriculture)
The experiment was carried out at Albosife ( Near Mosul city ) in 2003 growing season to determine the influnce of time , level of cutting and their interaction on growth of Johnson grass . Date were subjected to the conventional analysis randomized complete block design ( R ، C ، B ، D)as a factorial experiment with three replicates . The result showed that the cutting plant at 5 or 10 cm above the soil had markedly depressed the dry weight of plant and rhizomes if it compared with out cutting treatment . Also the frequent cutting at every 10 days was more effect on plant growth than 20 or 30 days if it used as a method for it control . It reduced the length of rhizome up to 98.6 , 78.8 and 55.6 % respectively and 98.2 , 77.8 and 50.6 % for number of buds on rhizome . On other hand the same treatment ( cutting every 10 days ) had excellent in decrease in D . W . of plant growth and rhizomes which reduced up to 96 , 94.3 , 84.9 % for D . W . of plant growth and 99.7 , 91.9 68.2 % for D . W . of rhizomes . The best result interaction between two factors was the frequent time of cutting of every 10 days which cutting near the soil surface .